Pink guava (psidium guajava) puree supplement on high fat diet-induced obese rats: effects on antioxidant enzyme activities, kidney and liver functions (supplemen puri jambu batu merah (psidium guajava) ke atas tikus teraruh obesiti: kesan terhadap aktiviti enzim antioksidan, fungsi ginjal dan fungsi hati) - Ayub Mohd Yatim,; Norazmir Md Nor, (Universiti Kebangsaan Malaysia, 2011)
In this study, the effect of pink guava (Psidium guajava) puree supplementation on antioxidant enzyme activities, kidney and liver functions in High Fat Diet (HFD)-induced obese rats was investigated. Thirty male Sprague–Dawley rats were divided into control negative (CN) fed with rat pellet; control positive, low, medium and high dose group (CP, LDG, MDG and HDG) were fed High Fat Diet-AIN93G, respectively. CN and CP were given distilled water; while the treated group were given the aqueous puree, at concentration of 500, 1000 and 2000 mg/kg body weight, dissolved in distilled water were administered orally via a drinking bottle, respectively. Pink guava puree was supplemented with the HFD diet for six weeks. The rats were fasted overnight and euthanized under an anesthetic condition with ethyl ether, and blood was collected from the posterior vena cava at the end of experiment. A significant reduction in body weight was observed in the treated groups as compared to CN and CP group. Specific activities of glutathione peroxidase (GPx), glutathione reductase (GR) and superoxide dismutase (SOD) of the HFD-induced obese rats were significantly increased in comparison with the CN group. Kidney function test of urea concentration were significantly decreased in HFD-induced obese rats; LDG (4.28±0.69 mmol/L), MDG (4.35±0.87 mmol/L) and HDG (3.85±0.71 mmol/L) as compared to CN (7.02±1.81 mmol/L), respectively. Liver function tests for total protein, globulin, A:G ratio and alanine aminotransferase (ALT) showed significant differences in the treated group compared to CN group. Total protein of MDG (72.67±3.65 g/L) and HDG (76.00±2.49 g/L) were significantly lower compared to CN (80.11±1.98 g/L). Globulin value for LDG (34.17±3.43 g/L), MDG (32.17±1.83 g/L) and HDG (35.00±3.41 g/L) were significantly lower compared to CN (39.67±0.82 g/L). A:G ratio LDG (1.22±0.16), MDG (1.28±0.07) and HDG (1.19±0.14) significantly different compared to CN (1.03±0.08). ALT value for LDG (55.83±15.12 U/L), MDG (50.67±22.65 U/L) and HDG (57.50±8.48 U/L) were significantly lower compared to CN (77.00±16.26 U/L), respectively. In conclusion, pink guava puree supplements seem to be beneficial for increased antioxidant enzyme activities and correcting/ preventing obesity complications in kidney and liver functions